Pendidikan Multi Kultural Dalam Al-Qur’an - Dahari Dahari (STAI Asy-Syukriyyah, 2018)
Multicultural education emerged as part of the response to the phenomenon of ethnic, social, and cultural conflicts that often emerged in the middle of multicultural faced communities. Multiculturalism is an understanding of the acceptance of pluralism in society so as to avoid horizontal conflict in society. The concept of multicultural education emphasizes the cultivation of a respectful, sincere and tolerant way of life towards the diversity of cultures that live in the midst of a pluralistic society. The goal of multicultural education is to be able to produce generations of people beside being knowledgeable and skilled can also live together in society as khoiru ummah (the best society).